The RRI Citizen Review Panel: A public engagement method for supporting responsible territorial policymaking - Maya Vestergaard Bidstrup; Snezhina Gabova; Pavlos Kilintzis; Elpida T. Samara; Amalia Kouskoura; Yiannis Bakouros; Florian Roth (Journal of Innovation and Entrepreneurship, 2024)
Responsible Territorial Policymaking incorporates the main principles of Responsible Research and Innovation (RRI) into the policymaking process, making it well-suited for guiding the development of sustainable and resilient territorial policies that prioritise societal needs. As a cornerstone in RRI, public engagement plays a central role in this process, underscoring the importance of involving all societal actors to align outcomes with the needs, expectations, and values of society. In the absence of existing methods to gather sufficiently and effectively the citizens' review of multiple policies at a territorial level, the RRI Citizen Review Panel is a new public engagement method developed to facilitate citizens' review and validation of territorial policies. By using RRI as an analytical framework, this paper examines whether the RRI Citizen Review Panel can support Responsible Territorial Policymaking, not only by incorporating citizens' perspectives into territorial policymaking, but also by making policies more responsible. The paper demonstrates that in the review of territorial policies, citizens are adding elements of RRI to a wide range of policies within different policy areas, contributing to making policies more responsible. Consequently, the RRI Citizen Review Panel emerges as a valuable tool for policymakers, enabling them to gather citizen perspectives and imbue policies with a heightened sense of responsibility.
Keywords: 650; AIRR; Inclusiveness; Public engagement; RRI; RRI Citizen Review Panel; Territorial policymaking